Recrystallisation before austenitization for improved microstructure and properties in automotive steel sheets with high product of strength and elongation. (12th May 2021) - Huang, Fei; Zhang, Heng; Qi, Jialin; Chen, Qiwei; Ding, Hanlin
Abstract: This study investigated the effect of recrystallization before austenitizing transformation (i.e., pre-recrystallization) on the microstructure and properties of 22Mn2Cr cold-rolled automotive steel sheets based on continuous annealing at 700 °C for various holding times. Subsequently, the samples were heated to an austenitizing temperature of ∼850 °C, which led to the formation of a fine austenite grains via nucleation at the dislocations during reheating. The austenite grain size was more refined when samples were pre-recrystallized at 700 °C for several minutes compared to those directly heated to 850 °C, which was attributed to combined grain refinement from recrystallization and austenite phase transformation. This refined austenite grain size led to a finer bainite grain size in the cooled final product. The strength of the steel decreased slightly (∼1200 MPa), but the elongation (∼19%) and product of strength and elongation (∼23 GPa%) were significantly enhanced by the pre-recrystallization treatment.